ISLAMIC CHARACTERED EDUCATION FACED WITH SOCIAL BEHAVIOR IN GENERAL SCHOOLS - Ali Akbarjono; Irwan Satria; Abdul Wahab Syakhrani; Fuadah Johari (International Journal of Teaching and Learning, 2024)
The study aims to analyze the impact of Islamic character education on social behaviour of students in public schools. With increasing attention to the importance of student moral and character development in the educational environment, Islamic character approach has become one of the methods taught in public schools. The applied Islamic character education is expected not only to enhance students' understanding of religion but also to shape positive and productive social behavior in their daily lives. The research uses a method of literary study, in which data and information are obtained through the collection of relevant sources from both books, scientific journals, articles, as well as online publications related to Islamic character education and its influence on student social behavior. Research results show that Islamic character education plays an important role in the formation and development of positive social behavior of students, which is beneficial not only to the individual students themselves but also to the environment around them, including the school community and society at large. Islamic character education not only teaches students about Islamic values but also prepares them to be responsible, empathic, and productive individuals in society.